129k views
5 votes
-5×(-5)^7×(-5)^6 simplified into exponential form

1 Answer

7 votes

We are to convert the answer from the workings into exponential form. We can do this by understanding the exponent of each. When the base are equal we can add the the exponents (powers) together.

-5×(-5)^7×(-5)^6 = (-5)^1 ×(-5)^7 × (-5)^6

Now from the above, we have exponent 1 , 7 and 6

When we add the exponents, we have= 1+7+6 = 14

The simplification of the above expression becomes:

(-5) raised to the power of the summation we obtained

In otherwords, -5×(-5)^7×(-5)^6 = (-5)^14

The simplification of -5×(-5)^7×(-5)^6 = (-5)^14

The answer = (-5)^14

User Yograj Gupta
by
6.1k points